Idle Expenditure on Medical Equipment at Base Hospital, Almora, Uttarakhand - CAG of India (CAG of India, 2015)
Medical equipment worth ₹ 60.52 lakh were not put to use for the benefit of patients and kept idle for periods ranging from six to eight years.